Impact of age and gender on the safety and efficacy of chemotherapy plus bevacizumab in metastatic colorectal cancer: a pooled analysis of TRIBE and TRIBE2 studies. (1st October 2019) - Marmorino, F; Rossini, D; Lonardi, S; Moretto, R; Zucchelli, G; Aprile, G; Dell'Aquila, E; Ratti, M; Bergamo, F; Masi, G; Urbano, F; Ronzoni, M; et al.
Abstract: Background: The phase III TRIBE and TRIBE2 studies randomized metastatic colorectal cancer patients to first-line FOLFOXIRI/bevacizumab or a doublet (FOLFIRI or FOLFOX)/bevacizumab. The studies demonstrated a significant benefit from the triplet at the price of an increased incidence of chemotherapy-related adverse events (AEs). In both trials, males and females aged between 18 and 70 years with ECOG PS ≤2 and between 71 and 75 years with ECOG PS = 0 were eligible. We investigated the effect of FOLFOXIRI/bevacizumab versus doublets/bevacizumab according to age and gender. Patients and methods: Subgroup analyses according to age (<70 versus 70–75 years) and gender were carried out for overall response rate (ORR), progression-free survival (PFS), and AE rates. Results: Of 1187 patients, 1005 (85%) were aged <70 years and 182 (15%) 70–75 years; 693 (58%) were males and 494 (42%) females. There was no evidence of interaction between age or gender and the benefit provided by the intensification of the upfront chemotherapy in terms of ORR and PFS, or the increased risk of experiencing G3/4 AEs. Elderly patients and females experienced higher rates of overall G3/4 AEs (73% versus 60%, P < 0.01 and 69% versus 57%, P < 0.01, respectively). Notably, in the FOLFOXIRI/bevacizumab subgroup, G3/4 diarrhea and febrile neutropenia occurred in 27% and 16% of elderly patients, respectively, while females reported high incidences of any grade nausea (67%) and vomiting (50%). Conclusions: The improvements in terms of ORR and PFS of FOLFOXIRI/bevacizumab versus doublets/bevacizumab are independent of gender and age, with a similar relative increase in AEs among elderly patients and females. Initial dose reductions and possibly primary G-CSF prophylaxis should be recommended for patients between 70 and 75 years old treated with FOLFOXIRI/bevacizumab, and a careful management of antiemetic prophylaxis should be considered among females.